Sleep Deficiency Is Associated With Exacerbation of Symptoms and Impairment of Anorectal and Autonomic Functions in Patients With Functional Constipation - Liu, Jie; Wang, Wei; Tian, Jiashuang; Lv, Chaolan; Fu, Yuhan; Fass, Ronnie; Song, Gengqing; Yu, Yue (Frontiers in Neuroscience, 2022)
Background: Sleep deficiency (SD) is commonly seen in patients with functional constipation (FC). Our aim was to determine whether the presence of SD would influence symptoms, anorectal motility, sensation, and autonomic function in FC patients. Methods: A total of 85 FC patients with SD and 193 FC patients without SD underwent high-resolution anorectal manometry. SD was assessed by using the Pittsburgh Sleep Quality Index (PSQI) score. Participants were required to fill in the entire questionnaires, including Patients’ Constipation-symptoms, State-Trait Anxiety Inventory, and Hamilton Depression Scale. Autonomic dysfunction was studied by recording the heart rate variability. Multiple logistic regression was performed to explore the potential risk factors for anorectal function. Results: FC patients with SD had a higher total score of constipation symptom (P<0.001), in comparison with those without SD. FC patients with SD demonstrated significantly lower threshold volume for first sensation (P<0.001) and urge (P<0.001), as compared to those without SD. The PSQI score positively correlated with constipation symptom total score (P<0.001), and negatively correlated with threshold volume for first sensation (P<0.001) and urge (P<0.001). FC patients with SD had a reduced vagal activity as compared to those without SD (P=0.016). Multivariate logistic regression revealed that SD, anxiety and depression were independent risk factors for anorectal function, with SD exhibiting the highest degree of association with first sensation (OR: 4.235). Conclusions: SD is associated with worse constipation related symptoms, altered anorectal function and perception, and impaired autonomic function in FC patients.